Organismo e sujeito: uma diferença sensível nas paralisias cerebrais - Vasconcellos, Roseli (2010)
This study discusses issues related to the distinction between the body conceived as an organism and the body approached as parlêtre (Lacan s expression). This subject-matter emerged from my clinical practice carried on with persons with Cerebral Palsy (CP). It is assumed that a theoretical dialogue with the fields of Medicine (Neurology) and with the Speech Pathology and Therapy is necessary and extremely relevant. Therefore, two chapters were dedicated to the literature of those areas. Recent papers and manuals, concerning CP, were selected. It is pointed out that the most recent research conclusions suggest, in fact, a strong convergence between what is taken as new and what is said to be old knowledge in the field of CP. Freud s statement, written in 1897, should, no doubt, be viewed as up-to-date. Some critical comments related to the Alternative Communication Systems (CA) were also included and a brief presentation of the Blissymbols and the Picture Communication Symbols (PCS) were followed by considerations about their importance for the Language Clinic theoretical development. I tried to point to the fact that such a Clinic takes clear distance from all others, since the CA introduction is guided by the specific language and subject conceptions assumed in this study. The theoretical orientation, here assumed, allowed me to address the problematic distinction between organic body and language body. This doctoral dissertation, which departs from the clinical practice with persons with Cerebral Palsy, is committed to the theorization undertaken in the CNPq Research Group, headed by Maria Francisca Lier-DeVitto, at LAEL PUCSP. It must be said that the Language Clinic is affiliated to the Interacionism in Language Acquisition, proposed by Cláudia de Lemos. Such a theoretical framework has strong links with the so called european structuralism as interpreted by Jacques Lacan. Such a theoretical trend triggered the inclusion of the psychoanalytical reflection on the subject speaker and about the relationship between child-language-speech. The difference this study introduces is illuminated by the clinical effects of the implementation of Alternative Communication Systems. It is worth saying that it is the therapist s body and speech that provide and support the materialization of the significant. The heterogeneous clinical effects analyzed led to considerations about the nature of listening, about transference and about the tension between conflict and pleasure that accompany some subtle and fragile vocalized speech. Data were discussed here and the interpretation conveyed sustains, I believe, the clinical and theoretical supposition proposed and advanced in this doctoral dissertation, i. e., that the body as organism and the body as parlêtre do not coincide